القدرة المكانية وعلاقتها بالأداء التحصيلي في الرياضيات - بهلول, خديجة; رحماوي, سعاد (جامعة الوادي - University of Eloued, 2022)
الملخص: تهدف دراستنا الحالية إلى البحث في العلاقة بين القدرة المكانية والأداء التحصيلي في الرياضيات لدى تلاميذ السنة أولى متوسط، وكذا تحري الفروق بين الإناث والذكور في مستوى القدرة المكانية. وذلك من خلال دراسة ميدانية تبنينا فيها المنهج الوصفي التحليلي على عينة قوامها 77 تلميذ وتلميذة، طبقنا فيها اختبار المصفوفات المتتابعة الملونة كاختبار للقدرة المكانية، واعتمدنا على علامات اختبار مادة الرياضيات للثلاثي الثاني كمستوى للأداء التحصيلي في الرياضيات، وبعد معالجة البيانات احصائيا أسفرت النتائج على وجود علاقة ارتباطية دالة احصائيا بين القدرة المكانية والأداء التحصيلي في الرياضيات، إلى جانب وجود فروق ذات دلالة احصائية عند مستوى الدلالة 0.05 بين التلاميذ في مستوى القدرة المكانية تعزى لمتغير الجنس ولصالح الإناث. Abstract: Our actual study aims at looking for the relationship between the spatial ability and the achievement performance in Mathematics for the first year students in the Middle School. Besides, it aims at the differentiation between the spatial ability for boys as well as girls through empirical study in which we adopted the descriptive analytical approach on 77 pupils. We applied the color Sequential matrix test as a test about the spatial ability. Also, we adopted the Mathematics examination marks in the second trimester as level for the achievement performance in Mathematics. After treating the data statistically, the results showed the existence of a statistically significant relationship between the spatial ability and the achievement performance in Mathematics. Besides, we noticed the existence ofa statistically significant differences at the indication level of 0.05 between the pupils in the level of the spatial ability attributed to a variable of sexin favor of girls.
مقال
Keywords: القدرة المكانية ; الأداء التحصيلي ; الرياضيات; spatial ability; achievement performance; Mathematics